The Effect of Massed Practice on Free Shots at POPDA Kepahiang Basketball Athletes - Deffri Anggara; Megi Personi (Hanoman Journal: Physical Education and Sport, 2022)
The purpose of this research is to determine the effect of massed practice training on free shots by POPDA Kepahiang basketball athletes. The method used is a quasi-experimental method by providing mass practice training to POPDA Kepahiang athletes and free shot tests. Massed Practice training has a significant influence on the free throws of POPDA Kepahiang basketball athletes. In the Massed Practice post test results, there was an increase in free throw results where the increase was 1.4, namely from 4.3 in the pre test to 5.7 in the post test. This increase is likely due to continuous adaptation and training from Massed Practice training on the body organs that support the increase in free shots, such as skeletal muscles, flexibility of movement and confidence with the ball so that they can direct it in the right direction or position for a free shot. can get into the ring which is the goal of the game of basketball.